A new genus and species of tarsonemid mite (Acari: Tarsonemidae) from Brazil - Lofego, Antonio C.; Feres, Reinaldo J.F. [UNESP] (My University, 2006)
Biscutulumnemus neotropicus gen. nov., sp. nov. (Tarsonemidae: Tarsoneminae: Tarsonemini) is described from adult female and male mites, collected on Croton floribundus Spreng., from São José do Rio Preto, State of São Paulo, Brazil. This new genus resembles members of Dendmptus and Tarsonemus, but male mites have two triangular shields anterolaterally to the prodorsal shield and the sejugal apodeme is absent. In addition, Biscutulumnemus differs from Dendroptus by the presence of femoral seta l″ and tibial solenidion φ1 and the presence of a vestigial apodeme I on female mites. Unlike Tarsonemus, Biscutulumnemus has a beaklike gnathosomal capsule, a round flange on leg IV of male mites, and stigmata very close to v1 on the prodorsal shield of female mites. Copyright © 2006 Magnolia Press.
Keywords: Biscutulumnemus; Neotropicus; New species; Tarsoneminae; Tarsonemoidea; Taxonomy; Acari; Croton floribundus; Tarsonemidae; Tarsonemus